An Evaluation of Topology Effect on Tiny Service Discovery Protocol for Wireless Sensor Networks - Kahloot, Khalid; ElKhatib, Akram A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In the literature of wireless sensor networks (WSNs), a well studied problem is that of achieving full sevice discovery within a region according to the topology model of coverage. A large waiting time of wireless sensor applications spent in node discovery, as nodes need to periodically advertise their presence and be awake to discover other nodes for services. Uniformly random distributions are widely accepted models for the location of the nodes in WSNs. Depending on the application, it may also be possible to place sensors in a four models of topologies; random, square, tringle and hexagon. Â There is a rich literature on throughput capacity for WSNs topologies in general, but we want to specifically study Service Discovery Protocol and how proper node deployment scheme can reduce the complexity of problems. In this paper, the effect of node topology on the performance of Tiny Service Discovery Protocol (TinySDP) in WSNs has been analyzed. In order to measure and evaluate the performance of TinySDP within variant shapes of topologies, We compared in terms of success ratio, number of transmitted messages and average waiting time. Simulation results showed that hexagon topology has a high data success ratio and a very low average waiting time, which are major requirements for disaster management scenarios.Â Â